(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The industry collaboration with institution is a long back talk, but it goes every year as emerging talk in the field of academic and the education world. Because its parallel travel not yet completed. So, the present article tries to address why industry and academia collaboration is a matter and how various researcher have addressed the matter and what was their findings. This will help the present and future researcher in the field to frame conceptual model, attributes and available gap. It is purely an analytical study. The present article discusses about why it’s a matter, importance and benefits and various national and international researcher findings. The researcher of this article is taking research in addressing the connecting local industries for local employment.